Enhancement of Wear Resistance by β-Precipitates Formation on A7075/WC/ZrSiO4 Surface Composites Fabricated Through FSP - Patel, Surendra Kumar; Raja, Avinash Ravi; Singh, Sudesh; Lei Shi, (International Journal of Integrated Engineering, 2024)
WC and ZrSiO4 nanoparticle-reinforced A7075 surface composites were fabricated using friction stir processing technique with 2, 4, and 6 passes. The microstructural analysis was performed by SEM, EDS, and XRD, which shows the better homogenous distribution of reinforcements into the A7075 surface matrix. The micro-hardness, tensile strength, and fatigue life were enhanced 60Hv, 167MPa, and 130000 cycles at 6 passes due to equally distributed formed ?-precipitates over the surface. Similarly, the surface wear resistance also increases with increasing the processing passes. The improved processed surface properties were highly useful in the marine and aerospace industries.